Spherical sliding isolation bearings with adaptive behavior Theory. - Fenz, Daniel M.
The principles of operation and force displacement relationships of three novel spherical sliding isolation bearings are developed in this paper. These bearings are completely passive devices, yet exhibit adaptive stiffness and adaptive damping. That is, the stiffness and damping change to predictable values at calculable and controllable displacement amplitudes. The primary benefit of adaptive behavior is that a given isolation system can be separately optimized for multiple performance objectives and/or multiple levels of ground shaking. With the devices presented here, this is accomplished using technology that is inherently no more complex than what is currently used by the civil engineering profession. The internal construction consists of various concave surfaces and behavior is dictated by the different combinations of surfaces upon which sliding can occur over the course of motion. As the surfaces upon which sliding occurs change, the stiffness and effective friction change accordingly. A methodology is presented for determining which surfaces are active at any given time based on the effective radius of curvature, coefficient of friction and displacement capacity of each sliding surface. The force displacement relationships and relevant parameters of interest are subsequently derived based on the first principles.
Keywords: Adaptive seismic isolation system; Triple friction pendulum bearing; Seismic isolation